Violence risk and personality assessment in adolescents by Structured Assessment of Violence Risk in Youth (SAVRY) and high school personality questionnaire (HSPQ): Focus on protective factors strengthening - Skřivánková, Petra; Páv, Marek; Faberová, Karolína; Perkins, Derek; Boukalová, Hedvika; Adam, David; Mazouchová, Aneta; Gillernová, Ilona; Anders, Martin; Kitzlerová, Eva (Frontiers in Psychiatry, 2023)
Background Adolescents are most at risk of engaging in violent interaction. Targeting violence risk and protective factors is essential for correctly understanding and assessing their role in potential violence. We aimed to use the Structured Assessment of Violence Risk in Youth (SAVRY) tool within the sample of adolescents to capture violence risk and protective factors and personality variables related to risk and protective factors. We further aimed to identify which violence risk and protective factors were positively or negatively related to violence within personal history and if any personality traits are typical for violent and non-violent adolescents. Identifying broader or underlying constructs within the SAVRY tool factor analysis can enable appropriate therapeutic targeting. Methods We used the Czech standardized version of the SAVRY tool. The study sample comprised 175 men and 226 women aged 12–18 years divided into two categories according to the presence or absence of violence in their personal history. Mann-Whitney U test was used to compare numerical variables between the two groups. SAVRY factor analysis with varimax rotation was used to determine the item factors. We administered the High School Personality Questionnaire (HSPQ) to capture adolescents’ personality characteristics. Results In our sample, there were 151 participants with violence in their personal histories and 250 non-violent participants. Non-violent adolescents had higher values for all six SAVRY protective factors. The strongest protective factor was P3, Strong attachment and bonds across gender or a history of violence. Using factor analysis, we identified three SAVRY internal factors: social conduct, assimilation, and maladaptation. The SAVRY protective factors were significantly positively related to several factors in the HSPQ questionnaire. Conclusion The results highlight the significance of protective factors and their relationship with violence prevalence. HSPQ diagnostics could be helpful in clinically targeting personality-based violence risks and protective factors. The therapeutic focus should be on tension, peer rejection, and anxiety. It is also essential to foster positive attitudes toward authority, prosocial behavior, and attitudes toward school. These strategies can help strengthen protective factors of the SAVRY.